A comprehensive analysis of a patient with anterior interosseous nerve neuropathy - Josivaldo De Souza Lima; Pedro Valdivia-Moral; Sandra Mahecha-Matsudo; Victor Keihan Rodrigues Matsudo; Mauro Rumbaut; Gerson Ferrari; Frano Giakoni-Ramirez (Revista Cubana de Medicina Militar)
Introduction: Isolated anterior interosseous nerve paralysis, initially characterized by Parsonage and Turner in 1948, evolved with Kiloh and Nevin's 1952 identification, leading to the term "Kiloh-Nevin syndrome." Recent cases prompted a comprehensive review, emphasizing accurate differentiation for tailored therapeutic guidance and improved patient outcomes, incorporating advanced imaging techniques like magnetic resonance imaging. Objective: To present the clinical case of a patient with anterior interosseous nerve paralysis (Kiloh-Nevin syndrome). Clinical case: A 44-year-old right-handed man, physically active, participates in functional training thrice weekly and amateur soccer. His perceived exertion ranges from "hard" to "very hard" on the Borg scale. He also works a sedentary office job. The patient suddenly exhibited an inability to flex his left thumb and perform an "OK" sign, with no identifiable preceding event. Conclusion: The case of anterior interosseous nerve palsy in an active patient highlights the importance of recognizing peripheral nerve injuries in such individuals. Interactions between a sedentary job and physical activities suggest a multifactorial nature. Advanced diagnostic modalities aid in accurate diagnosis.